Adrenal Failure due to Adrenal Metastasis of Lung Cancer: A Case Report - Gustavo Adolpho Moreira Faulhaber; Flavia Kessler Borges; Aline Maria Ascoli; Renato Seligman; Tania Weber Furlanetto (Case Reports in Oncological Medicine)
We report a case of a patient with adrenal failure due to bilateral adrenal metastasis of lung cancer. This is a rare presentation of lung cancer. We review the differential diagnosis of weight loss and how to make diagnosis of adrenal insufficiency.